الآيات الكونية والغيبيات في تفسير عبدالله الطيب Qur’anic verses related to natural phenomena and eschatological matters in the commentary of Abdulla El-Tayeb - إبراهيم (Esam Eltigani M. Ibrahim) عصام التجاني محمد (At-Tajdid - Intellectual Refereed Journal, 2009)
Abstract The aim of this article is to provide a systematic account on Abdulla El-Ùayeb El-Majdoub and his tafsÊr methodology in dealing with Qur’anic verses pertaining to natural and cosmological phenomena as well as verses concerning eschatological matters. The article also discusses the most important drawbacks held against Abdulla El-Ùayeb, which is the colloquial dialect that he used in his tafsÊr. The article relied on analytic and inductive methods in heating the subject. One of these results was that his methodology of his tafsÊr for the verses related to the cosmos depended primarily on dictum from the Qur’Én and Sunnah. Furthermore, he did not entertain the stories of the people of Israel (Israelite) in his tafsÊr of the verses of death and the afterlife and the unseen. مستخلص البحث يهدف هذا البحث إلى دراسة شخصية الدكتور عبد الله الطيب المجذوب وبيان منهجه في تفسير الآيات الكونية والغيبيات. وقد تناول البحث أهم المآخذ على عبد الله الطيب كاستخدامه اللهجة العامية (الدارجة) في تفسيره. وقد اعتمد البحث على منهجي الاستقراء والتحليلي الاستنباطي للوصول إلى النتائج المرجوة. ومن نتائج البحث أن المنهج الذي سار عليه الدكتور عبد الله الطيب رحمه الله في عرضه للآيات الكونية في القرآن، أو ما يسمى بالتفسير العلمي، يتسم بعدم الإشارة إلى العلوم الكونية المختلفة، الفلكية منها والطبيعية، وفي الحالات النادرة التي يشير فيها إلى العلوم الكونية نجده يذكرها بإيجاز شديد ويتجنب الإسهاب والاطالة في استحضار تلك العلوم، فهو في ذلك سلك مسلك العلماء الرافضين للتفسير العلمي. وأما طريقته في تفسيره لآيات الموت والآخرة والغيبيات، فخلاصة منهجه في ذلك أنه يفسرها بالقرآن والسنة واللغة، بعيداً عن الإسرائيليات والخيالات والأوهام.